2014
DOI: 10.1177/0959683614544056
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between water and air temperature in chironomid-based paleoclimate reconstructions: Records from boreal and subarctic Finland

Abstract: Fossil remains of larval chironomids are one of the most useful paleolimnological proxies to reconstruct Holocene paleoclimate. We investigate the within-lake distribution of chironomids in relation to water temperature and test the usability of intralake calibration in chironomid-based temperature reconstructions. We compare our findings against the traditional multilake calibration technique in Holocene sediment cores from Finland. The results show that intralake water temperature optima of common taxa corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…É. SAULNIER-TALBOT et al NIER-TALBOT et al Overall, we found evidence for reliable chironomidbased inferences of temperature trends for the region, especially from the two headwater lakes. �hese findings are consistent with the well-established relationships between chironomids and both air and water temperature at high latitudes (Brodersen and Lindegaard, 1999;Luoto et al, 2014). Indeed, many studies have illustrated the accuracy of using chironomids for quantitatively reconstructing air temperature.…”
Section: Discussionsupporting
confidence: 77%
“…É. SAULNIER-TALBOT et al NIER-TALBOT et al Overall, we found evidence for reliable chironomidbased inferences of temperature trends for the region, especially from the two headwater lakes. �hese findings are consistent with the well-established relationships between chironomids and both air and water temperature at high latitudes (Brodersen and Lindegaard, 1999;Luoto et al, 2014). Indeed, many studies have illustrated the accuracy of using chironomids for quantitatively reconstructing air temperature.…”
Section: Discussionsupporting
confidence: 77%
“…A major factor influencing chironomid communities is lake-level changes (Engels and Cwynar, 2011) that could potentially compromise the reliability of the reconstruction. However, a study on boreal lakes has shown that since the inlake water depth gradient is usually directly linked with the water temperature profile, it has the same control on chironomid distribution as the air temperature gradient at large spatial gradients (Luoto et al, 2014). In addition to hydrological conditions, dissolved organic carbon (DOC) and lake humic state have significant influence on chironomid communities (Larocque et al, 2006; Luoto, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the study region, discrepancies between the pollen and other sedimentary proxy records have recently been related to inaccuracies in the models transforming the pollen data into temperature estimates, to climatic disequilibrium of vegetation migration patterns, and to site-specific factors (Luoto et al, 2014b;Shala et al, 2017). Chironomid-based records, however, may be affected by limnic factors (Luoto et al, 2014a).…”
Section: Differing Signals Of Orbital Forcingmentioning
confidence: 99%